Development of Multilingual Educational Game UI/UX Design for Animal Introduction and Interactive Learning Evaluation in Elementary Schools - Krisdiawan, Rio Andriyat; Husen, Dede; Asikin, Nida Amalia (Bina Nusantara University, 2025)
Technology-based education plays a vital role in enhancing student engagement in the digital age. This research focused on creating a UI/UX design and prototype for a multilingual educational game tailored for elementary school students. The game emphasizes animal recognition in both English and Indonesian, categorizing animals into herbivores, carnivores, and omnivores, while also featuring interactive learning evaluations. The study utilized the Design Thinking framework, which comprises five stages: Empathize, Define, Ideate, Prototype, and Test. Data collection involved surveys and interviews with 60 students and 3 teachers. The findings revealed positive feedback, with students giving high ratings for visual appeal (4.65), ease of navigation (4.52), and learning effectiveness (4.47). Teachers also rated the game highly for ease of use (5.0) and its suitability for students' needs (4.67). However, the interactive evaluation component requires improvement, particularly in diversifying question types and offering more adaptive feedback. This research highlights the potential of thoughtfully designed educational games to enhance student motivation and comprehension. Future recommendations include enriching content, increasing platform accessibility, and collaborating with schools for broader implementation.